Evaluation of Salivary Cytomegalovirus and Epstein–Barr Virus Antibody Levels in Recurrent Aphthous Stomatitis: An Analytical Cross-Sectional Study - Sura Farhan Saeed; Zainab A. Aldhaher (Dental Hypotheses)
Introduction: We aimed to investigate the salivary cytomegalovirus (CMV) and Epstein–Barr virus (EBV) antibody levels among patients with recurrent aphthous stomatitis (RAS). Methods: Eighty subjects were participated in this study: 40 patients with RAS and 40 healthy persons. A saliva sample was taken from each group for evaluation of salivary levels of CMV and EBV IgG by using a sandwich enzyme-linked immune-sorbent assay. Results: Salivary levels of CMV (P = 0.072, mean difference: −0.174, 95% confidence interval: −0.364 to 0.0161) and EBV (P = 0.004, mean difference: −0.291, 95% confidence interval: −0.488 to −0.0943) IgG among patients with RAS were significantly higher than healthy subjects. Conclusion: This study emphasizes that CMV and EBV infections may associated with the etiology of RAS.